Bhāyasi maṃ samaṇā – „Boisz się mnie, asceto?” O rozmowach jakszów (demonów) z Buddą i ich nawróceniach w kanonie palijskim - Betka, Alicja (2024)
Yakshas are mythical beings connected to the powers of nature, present not only in Hinduism, but also in Buddhism. In the early Buddhist literature of the Theravada school (Pali Canon) there are some fragments, in which yakshas meet Buddha or his disciples and are converted to Buddhism. The suttas with yakshas as main characters appear chiefly in Saṃyutta Nikāya 10.1–12 and Sutta Nipāta 1.9 –10, 2.5 which are the research material for this paper. A close reading of these texts proposed in this article as well as examination of historical background are aimed at analyzing the relation between demons and Buddha, the motivations of yakshas and their conversion to Buddhism. The investigation leads to an understanding of the role of the yakshas’ conversions in the Pali Canon by answering these questions: Why and under what circumstances do yakshas meet Buddha? Why do yakshas ask Buddha questions? What is his reaction after meeting yakshas, and how do yakshas react when they see Buddha? How does yaksha transform after conversion?
Keywords: Buddhist literature; Pali Canon; Buddha; yakshas